Islamic and Senior High Schools in School Market in Indonesia - Juhaidi, Ahmad; Bainah, Bainah; Tajudin, Anas; Munadi, Muhammad (research, training and philanthropy institution Natural Aceh, 2024)
Madrasah and non-religious schools must compete for potential students. These two types of educational institutions compete to attract similar student markets. Therefore, this article aims to explore the strategies of madrasah aliyah (MA) and high school (SMA) in the school market in the local context. In addition, this article aims to explore the positioning, differentiation, and brand (PDB) strategies of MA and SMA in the local context. This research is qualitative. Data was collected using interviews with 16 participants: principals, vice principals, teachers, students, alums, parents, and villagers. The study found the number of MA students declined more than high school students in the past five years. Moreover, the findings of this study show that MA PDB focus on Islamic religious learning and skills is different from the market's expectations: students/parents. In contrast, the GDP chosen by SMA focuses more on academic achievement and further study by the expectations of students and parents. This research suggests that madrasahs and schools analyze market needs for sustainable education as a basis for marketing strategies. The study also suggests a study to verify the effect of PDB on enrolment intention